Stepfamily therapy a 10-step clinical approach - Browning, Scott (American Psychological Association, 2012)
"Because stepfamilies present in many variations--married or cohabiting; gay, lesbian, or straight; and with multiple ethnicities and religions--therapists need to have a starting point, a framework for treatment, and an ability to determine the priorities at hand as they learn more about the family. This book, Stepfamily therapy: A 10-step clinical approach, supplies a model and guidelines to provide therapists with confidence and strategies to tackle the challenging family configurations. Helping family members to examine their negative interactions and to come to the understanding that their feelings can be regarded as somewhat reasonable within the context of stepfamily adjustment provides a remarkable service. Herein is a rationale, supported by research and clinical and scholarly observation, for creating a way to decipher various issues that are idiosyncratic to stepfamilies"--Introduction. (PsycINFO Database Record (c) 2011 APA, all rights reserved)